Analisis Fungsi Koordinasi Kepala Desa Guna Meningkatkan Pembangunan Di Desa Sifalaete Kecamatan Gunungsitoli Idanoi - Erna Ningsih Laowo; Fatolosa Hulu; Palindungan Lahagu; Syah Abadi Mendrofa (Visi Sosial Humaniora, 2024)
Laowo, Erna Ningsih. 2024. Analysis of the Coordination Function of the Village Head to Improve Development in Sifalaete Village, Gunungsitoli Idanoi District. Undergraduate Thesis. Supervisor: Fatolosa Hulu, S.E., M.M. This research aims to examine the coordination function of the village head in improving development in Sifalaete Village, Gunungsitoli Idanoi District, particularly in the context of village development planning. Additionally, the study seeks to identify the challenges faced by the village head in coordinating efforts to enhance village development. The phenomenon observed is that the village head’s coordination in Sifalaete Village still encounters various challenges, including limited resources, lack of community participation, and ineffective coordination among involved parties. One of the main challenges identified is the disagreement of the Village Consultative Body (BPD) in signing the village development planning approval letter, which seriously impacts the development process in the village. This study employs a qualitative research method with a case study approach. Data were collected through in-depth interviews, observations, and documentation from various parties involved in the development process in Sifalaete Village. The findings indicate that the coordination function of the village head plays a crucial role in enhancing the effectiveness and efficiency of village development. However, there are significant challenges, such as ineffective communication between the village head and the BPD and low community participation in the development planning process. Based on the research findings, it is recommended that the village head and BPD improve cooperation and harmonious communication in planning and implementing village development. Moreover, efforts should be made to increase community participation at every stage of development to ensure a smoother process and more optimal outcomes. Better coordination is expected to address existing challenges and drive more effective development goals in Sifalaete Village.